2017
DOI: 10.1016/j.ophtha.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Visual Outcomes and Complications of Boston Keratoprosthesis Type II Implantation

Abstract: The Boston keratoprosthesis type II is a viable option to salvage vision in patients with poor prognosis for other corneal procedures. Retroprosthetic membranes, keratoprosthesis retention, and glaucoma are major challenges in the postoperative period; however, the keratoprosthesis can still provide improved vision in a select group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 44 publications
(38 reference statements)
1
57
0
1
Order By: Relevance
“…The device retention rates with Boston type II keratoprosthesis have been reported to be considerably lower than the MOOKP. In the most recent study, Lee et al 10 reported a 45.8% keratoprosthesis replacement rate after an average time interval of 3 years, mostly attributed to the occurrence of corneal melt. Pujari et al 8 had earlier reported an average survival rate of 58.6% during a follow-up period ranging from 1 to 5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The device retention rates with Boston type II keratoprosthesis have been reported to be considerably lower than the MOOKP. In the most recent study, Lee et al 10 reported a 45.8% keratoprosthesis replacement rate after an average time interval of 3 years, mostly attributed to the occurrence of corneal melt. Pujari et al 8 had earlier reported an average survival rate of 58.6% during a follow-up period ranging from 1 to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily for this reason that the authors had to abandon their MOOKP programme, as their retina and glaucoma colleagues struggled to effectively deal with postoperative problems that needed a retinal detachment repair or a glaucoma valve implantation. The current protocol for the Boston type II keratoprosthesis implantation includes simultaneous complete pars plana vitrectomy and Ahmed glaucoma valve implantation as prophylactic procedures 10. In eyes with the LVP Kpro, however, the retina surgeons were particularly comfortable in dealing surgically with posterior segment complications by injecting intravitreal drugs or making sutureless 23/25G ports directly through the mucosal graft.…”
Section: Discussionmentioning
confidence: 99%
“…Although Kpro type I surgery is more common, Kpro type II surgery is beneficial in patients with very severe ocular surface disease involving both the eyelids and ocular surface, such as those with extensive symblepharon, ankyblepharon, and ocular surface keratinization 5,7. The surgical method in type II keratoprosthesis implantation involves additional steps to the type I keratoprosthesis method,8 and consists of stripping of the bulbar and palpebral conjunctiva, shaping of the eyelids around the anterior extension of Kpro type II optic, and tarsorrhaphy to permanently close the eyelids around the keratoprosthesis optic 5…”
Section: Discussionmentioning
confidence: 99%
“…However, visual potential can be greatly limited by glaucoma, with a high reported prevalence of 64% to 76% before K pro surgery 37. In particular, glaucoma is more difficult to manage in Kpro type II patients compared with Kpro type I patients, because topical glaucoma medications have minimal ocular penetration in Kpro type II patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation